An Atherogenic Paigen-Diet Aggravates Nephropathy in Type 2 Diabetic OLETF Rats - Nozako, Masanori (PLoS One, 2015)
Diabetic nephropathy develops in association with hyperglycemia, is aggravated by atherogenic factors such as dyslipidemia, and is sometimes initiated before obvious hyperglycemia is seen. However, the precise mechanisms of progression are still unclear. In this study, we investigated the influence of an atherogenic Paigen diet (PD) on the progression of nephropathy in spontaneous type 2 diabetic OLETF rats. Feeding PD to male OLETF rats for 12 weeks caused an extensive increase in excretion of urinary albumin and markers of tubular injury such as KIM-1 and L-FABP, accompanied by mesangial expansion and tubular atrophy. PD significantly increased plasma total cholesterol concentration, which correlates well with increases in urine albumin excretion and mesangial expansion. Conversely, PD did not change plasma glucose and free fatty acid concentrations. PD enhanced renal levels of mRNA for inflammatory molecules such as KIM-1, MCP-1, TLR4 and TNF-α and promoted macrophage infiltration and lipid accumulation in the tubulointerstitium and glomeruli in OLETF rats. Intriguingly, PD had little effect on urine albumin excretion and renal morphology in normal control LETO rats. This model may be useful in studying the complex mechanisms that aggravate diabetic nephropathy in an atherogenic environment.